THE RESULT OF A HOLY ALLIANCE: DEBUS IN BANTEN PROVINCE - Rohman Rohman (Al Qalam, 2012)
This paper describes the practice of debus in Banten and its function among present-day Bantenese. The underlying question to be considered here is the way in which debus performances are now regarded as an integral part of Banten's tradition. There is a number of studies devoted to debus in Banten and in several places in Indonesia, most of which are anthropological studies. Little attention has been given to an in-depth study of debus practised the Bantenese. In fact, debus has developed as invulnerability performance and has gone much farther of late than the previous invulnerability performances in Aceh described S nouck at the end of the nineteenth century. I attempt to show how the debus performances combined with aspects of /ariqahi! now also include several new attributes.Key words: debus, tariqah, wird, Banten